The Efficacy of 3% Sodium Tetradecyl Sulphate (STS) Injection in Management of Intraoral Soft Tissue Vascular Lesion - Mirza Abdul Rauf, Shakeel Ahmad, Muhammad Muddassar, Rizwan Arshad, Imran Salem Qureshi, Kamal Khan Hoti (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the efficacy of 3% sodium tetradecyl sulphate (STS) in intraoral vascular lesions. Methods: Cross sectional study was done in oral and maxillofacial surgery department of Islam dental college from 1st Jan 2020 to 31st Dec 2021. 18 cases were selected with non-probability sampling technique.3% STS solution was intralesional injected. Site and size of lesion, pain intensity, burning sensation, tissue necrosis and area numbness variables were observed on preoperative,1stpostop, and then every 14th day until lesion subside and findings were documented in Performa. Results: Results were analysed statistically with SPSS version 23. Female 14 cases had predominance with 4 male cases. Mostly common site of lesion was tongue with 7 cases, 4 cases in cheek and 4 cases had involvement of lip area, 3 cases had lesion in the floor of mouth. 11 cases had mild pain, moderate pain in 5 cases and 2 cases with severe pain. 14 cases had burning sensation and 7 cases had tissue necrosis with area numbness. Conclusion: 3% Sodium tetradecylsulphate sclerosing agent usage is safe, cost effective and efficient to manage intraoral soft tissue vascular lesion. Although further studies are needed on large sampling data with longer follow-up. Keywords: Sodium tetradecyl sulphate, vascular lesion, haemangioma, sclerotherapy.